Meningkatkan Berpikir Kritis Siswa Melalui Penerapan Model Pembelajaran Inkuiri Sosial - Kurniasari, Ria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2021)
The research was conducted based on the low critical thinking of students in social studies learning. To overcome this problem, the researchers applied a social inquiry learning model. Social inquiry learning was a series of activities that emphasize critical thinking, analysis, and dialectical processes to seek and find the answer to a problem in question. This was developed through a strategy of asking questions, so that critical thinking skills have been developed since elementary education. Through this social inquiry learning, students have been trained to discover and reflect on the nature of social life. The method used was Classroom Action Research with Kemmis Mc Taggart design which consists of planning, implementation, observation and reflection stages. The subject in this research was 24 students in fifth grade SDN Sindang IV. The instruments used are observation sheets, interviews, field notes and tests. Based on the exposure to the data obtained, student activity and students' critical thinking increased. Thus it can be concluded that the application of social inquiry can improve students' critical thinking.